Running out of oxygen: the financial condition of Italian political parties - Chiara Fiorelli (QOE-IJES)
Electoral competition is quite expensive. The prevalent idea in Western countries is that public funding may contribute to and preserve the system’s fairness and pluralism, defending political parties from the influence of big money. However, the Italian reform of political funding approved in 2014 appears to move in an opposite direction, encouraging political players to extract private sources while discarding public support. Such a choice entails hazards associated with several current phenomena, including system transparency, financial appeals from competing players and the rising personalization of politics.